1998
DOI: 10.1017/s0043174500090214
|View full text |Cite
|
Sign up to set email alerts
|

Functional and quantitative analysis of seed thermal responses in prostrate knotweed (Polygonum aviculare) and common purslane (Portulaca oleracea)

Abstract: A screening method was used to characterize seed thermal responses of prostrate knotweed and common purslane, two important weeds invading wheat in the humid Pampa. Through this method, it was possible to detect thermal conditions that induce or break dormancy in both species. In addition, we were able to quantify changes in dormancy level in seed populations as a function of time of burial after dispersal, through changes in width of the thermal range within which germination can occur. Plotting the overlap o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 21 publications
5
48
0
Order By: Relevance
“…Under field conditions, P. aviculare seeds form persistent seedbanks and show seasonal changes in their dormancy status (Courtney, 1968; Baskin & Baskin, 1990). Kruk and Benech‐Arnold (1998) demonstrated that low temperatures alleviated dormancy, while high temperatures reinforced dormancy in seeds of this species. This thermal regulation of seed dormancy status under field conditions leads to a short emergence flush in spring, as seeds are released from dormancy during winter.…”
Section: Introductionmentioning
confidence: 87%
“…Under field conditions, P. aviculare seeds form persistent seedbanks and show seasonal changes in their dormancy status (Courtney, 1968; Baskin & Baskin, 1990). Kruk and Benech‐Arnold (1998) demonstrated that low temperatures alleviated dormancy, while high temperatures reinforced dormancy in seeds of this species. This thermal regulation of seed dormancy status under field conditions leads to a short emergence flush in spring, as seeds are released from dormancy during winter.…”
Section: Introductionmentioning
confidence: 87%
“…Remaining ungerminated seeds were later exposed to 25°C and daily alternating temperatures of 25°C (12h) / 12°C (12h) for 7 days at the end of the DT and IT regimes, respectively (Kruk and Benech-Arnold, 1998). Percentage germination attained immediately before seeds were subjected to either 25°C or 25°C/12°C was defined as 'final percentage germination' at that regime, while that attained after incubation at 25°C or 25°C/12°C was defined as 'maximum percentage germination'.…”
Section: Germination Test Systemmentioning
confidence: 99%
“…In relation to the first effect, the thermal environment may either increase or decrease the dormancy level of a seed population (Roberts, 1988). Dormancy cycles observed in some species are known to be regulated mainly by temperature Baskin, 1977, 1984;Bouwmeester andKarssen, 1992, 1993;Kruk and Benech-Arnold, 1998). For example, some summer annuals undergo dormancy relief by low temperatures experienced during winter, and their dormancy level is enhanced by high temperatures experienced during summer Baskin, 1977, 1984;Bouwmeester andKarssen, 1992, 1993;Kruk and Benech-Arnold, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good example of plasticity in a dormancy strategy can be found in Polygonum aviculare (prostrate knotweed). Seeds from this summer annual weed are dispersed with high dormancy at the end of the summer and become buried easily due to their small size . Low soil temperatures in autumn and winter release these seeds from primary dormancy if they are imbibed enough through the stratification process, determining the opening of an emergence window between mid‐winter and early spring.…”
Section: Seed Dormancy As a Trait For Adjustment: Stories Of Evolutiomentioning
confidence: 99%